All-of-a-kind family - Taylor, Sydney. 1904-; John, Helen (New York : Random House, Inc, 1989)
The adventures of five sisters growing up in a Jewish family in New York in the early twentieth century.
English language and literature.
Keywords: Family life -- New York (State) -- New York -- Fiction; Jews -- United States -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction